The involvement of the RET variant G691S in medullary thyroid carcinoma enlightened by a meta‐analysis study. Issue 12 (27th December 2012) - Lantieri, Francesca; Caroli, Francesco; Ceccherini, Isabella; Griseri, Paola
Abstract Medullary thyroid carcinoma (MTC) is a rare tumor, partially explained by mutations in the rearranged during transfection (RET) proto‐oncogene. The nonsynonymous RET polymorphism G691S has been reported as associated with MTC, but findings are discordant. We sought to clarify the role of G691S in MTCs through in silico analysis, genetic association in our patients and a meta‐analysis with extensive literature revision. Ninety‐three Italian patients were compared to 85 healthy individuals. Results were included in a meta‐analysis together with 11 case‐control association studies identified through PubMed, EMBASE and Web of Science, with a combined sample of 968 cases and 2, 115 controls. No association of G691S with MTC was found in our sample; however, we observed an excess of homozygotes for the variant, significantly higher among females. The overall allelic association in the meta‐analysis was significant under the fixed‐effect model (odds ratio [OR] = 1.22 [95% confidence intervals: 1.06–1.39], p = 0.0049), but borderline under the random effect model (OR = 1.21 [0.99–1.46], p = 0.0575), with a moderate/high heterogeneity (I2 = 44.6%, p = 0.047). Under the recessive model of transmission, applied to the eight studies with available genotype frequencies, results were significant under both effect models (OR = 2.016 and OR = 2.022, p = 0.0004). No heterogeneity was anymore detectable. In silico analyses on G691S confirmed a change of the phosphorylation pattern that might account for the enhanced signaling transduction previously reported for G691S in several cancers, thus also explaining its overrepresentation in MTCs. The G691S variant allele does increase the risk for MTC, with a recessive mechanism of action, apparently more evident among females.